If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 107 + -1x = -73 + -10x Solving 107 + -1x = -73 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 107 + -1x + 10x = -73 + -10x + 10x Combine like terms: -1x + 10x = 9x 107 + 9x = -73 + -10x + 10x Combine like terms: -10x + 10x = 0 107 + 9x = -73 + 0 107 + 9x = -73 Add '-107' to each side of the equation. 107 + -107 + 9x = -73 + -107 Combine like terms: 107 + -107 = 0 0 + 9x = -73 + -107 9x = -73 + -107 Combine like terms: -73 + -107 = -180 9x = -180 Divide each side by '9'. x = -20 Simplifying x = -20
| 7x-2(-x+17)=11 | | 7x+3(-4x-11)=-83 | | 150:2-40=x | | 30=3x(x-3) | | 10=X(X-3) | | -4(-2)=x | | 2+9=19 | | -2x+4x-2=3x-1 | | (5-6i)/(2+3i) | | 2+8=16 | | (2y^2x^0)/4 | | 2y^2x^0/4 | | 3x+19=11x-109 | | .22=8n^2 | | 2x^2+x-351=0 | | x+y=255 | | 59-x=77-7x | | x^3=9x^2 | | 3c+2=-19 | | 9y+18= | | 9y-18=0 | | 2y-3=20 | | 7a-4=30 | | V^2+6v-58=0 | | (2+x)(2+x)(2+x)=1 | | t-3/2=4-3t/4 | | x^2+y^2+z^2-2yz-2zx-2xy=c | | x/3-5=15 | | -0.5x=8 | | px*2+4x+6=0 | | 14x-2(-3x+9)=4(2x-7)-1 | | -(2x+13)=2(x+4) |